Study of Road Safety Audit in Sagar at Sironja Road as Per IRC-88 - A Review - Anupam Shrivastava,; Dharmendra Prajapati,; Anudeep Nema, (International Journal of Scientific Research in Civil Engineering, 2022)
Accidents are a drain on the national economy and may lead to disablement, death, damage to health and property, social suffering and general degradation of environment. To minimize the no of crashes by any kind and severity expected to occur on the entity during a specific period is known as road safety. Accidents and the fatalities on road are the result of inter-play of a number of factors. Road users in India are heterogeneous in nature, ranging from pedestrians, animal- driven carts, bi- cycles, rickshaws, hand carts and tractor trolleys, to various categories of two/three wheelers, motor cars, buses, trucks, and multi-axle commercial vehicles etc., The vehicle population has been steadily increasing because of change in the style of living of people. Increase in vehicle population with limited road space used by a large variety of vehicles has heightened the need and urgency for a well-thought-out policy on the issue of road safety. In India the rate of accident is directly proportional to growth of vehicle population.
Keywords: Road Safety; Blind Spots; Accident Prediction Model